Pengaruh Influencer Media Sosial terhadap Minat Beli Konsumen Fashion - Sabrina, Mila; Engriani, Yunita (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the influence of Informativeness, Credibility, Interactivity, Product Match Up, and Entertainment on consumer purchase intention, mediated by consumer attitudes toward the influencer Sashfir on social media, particularly in the fashion industry. This research employs a quantitative approach using Structural Equation Modeling (SEM). The study population consists of women actively using social media who have watched Sashfir’s videos. A purposive sampling technique was applied, resulting in 100 respondents determined using Cochran’s formula. Data were collected through questionnaires measured with a Likert scale. The findings reveal that all independent variables have a positive and significant effect on consumer purchase intention, both directly and through consumer attitudes as a mediating variable. These results highlight the crucial role of influencers with high credibility, informative content, active engagement, product relevance, and entertaining elements in shaping consumer attitudes and purchase intention. Consequently, this study contributes to the fashion industry and digital marketing strategies by providing insights into the effectiveness of influencers in attracting consumer interest through social media.